ANALISIS PENENTUAN LOKASI PENGEMBANGAN KLASTER INDUSTRI BERBASIS SINGKONG DI KABUPATEN JEMBER - Emi Kurniawati; Yuli Wibowo; Ida Bagus Suryaningrat (Faculty of Agricultural Technology, University of Jember, 2019)
Cassava-based industry in Jember Regency had good potential to be developed. The development could be done by forming industrial clusters. Cassava-based industrial clusters could be developed through determining potential locations. The study aimed to provide information about determining the location of the cassava-based industrial cluster development in Jember Regency. The study was conducted using the location quotient (LQ) method and the scalogram method. The results showed that the sub-districts in Jember Regency had potential locations for developing cassava-based industrial clusters, such as Kaliwates Sub-District, Patrang Sub-District, and Sumbersari Sub-District. The three sub-districts had advantages compared to other sub-districts in terms of the concentration of LQ values produced by cassava-based products. Scalogram results showed sub-districts in the highest service center hierarchy, i.e. Kaliwates Sub-District, Patrang Sub-District, and Sumbersari Sub-District. All three sub-districts had complete facilities compared to other sub-districts so that they could become centers of economy and trade. Based on the results of the LQ method and scalogram, the location of the cassava-based industrial cluster development in Jember Regency was determined in Kaliwates Sub-District, Patrang Sub-District, and Sumbersari Sub-District. Keywords: cassava, determination, development, location, industrial cluster